Can Fiscus Services and Tax Sanctions Improve Individual Taxpayer Compliance? - Wahyuni Wahyuni; Muhammad Adil; Nurul Fuada; Khadijah Darwin; Amran Amran (Advances in Taxation Research, 2023)
This study aims to determine the effect of tax services and tax sanctions on individual taxpayer compliance at KPP Pratama Watampone. This research was conducted at KPP Pratama Watampone. The number of samples taken is 100 taxpayers. The method used is accidental sampling. Data was collected by distributing questionnaires. Data were analyzed using multiple linear regression analysis. Based on the results of the study indicate that the tax service and tax sanctions have a positive effect on individual taxpayer compliance at KPP Pratama Watampone. The results showed that the tax service and tax sanctions could increase taxpayers at KPP Pratama Watampone.